The Lion, the Dragon and the Wardrobe Guarding the Doorway to Information and Communications Privacy on the Internet: A Comparative Case Study of Hong Kong and Singapore: Two Differing Asian Approaches - CHIK, Warren B. (Institutional Knowledge at Singapore Management University, 2005)
Almost a decade ago, the electronic commerce revolution began, led by such companies as Amazon.com and Ebay.com. These companies have grown into the internet business giants they are today, diversifying in the products they sell, the services they provide and the jurisdictions they conduct business in. However, aside from these rare examples, most medium and small internet-based business enterprises have grown with the dot.com bubble and dissolved when it burst mid-way through the decade. Now, at the 10th Anniversary of Electronic Commerce, after we have seen the dot.com way of doing business launch like a rocket and plunge like a comet, subsequently emerging into a more cautious, but no less potential, avenue of doing business, other challenges now face the industry as a whole to retain and obtain customers. Internet users are becoming increasingly wary of online transactions. 2 The irony is that as internet users become technologically savvy, they also become more aware of the dangers which connectivity entails and this inhibits their online behaviour. Chief among these concerns, and second only to cybercrimes, is the maintenance of privacy in the context of the protection of personal information, particularly from the unsavory elements trawling the cyberworld. For cyber-trade and the e-commerce market to grow, and for the continued efficiency and utility of the internet for G2C and B2C transactions, 3 governments and industries must re-instill the trust and confidence of internet users both in commercial and non-commercial interaction. 4